Visual perception and motor action: Issues in current quiet-eye research - Klostermann, A. (Sport and exercise psychology research: From theory to practice, 2016)
In recent years, research on the quiet eye (QE), that is, performance-enhancing long fixations before movement initiation, has been focused on proving its robustness in motor control and its advantages in motor learning. However, several issues in QE research remain that should be considered in future studies. After providing a brief introduction of the QE phenomenon, this work will focus on the need to apply more reliable methods of measurement to, for example, allow for increased trials and sample sizes. Afterward, it will be emphasized to work out theoretical explanations instead of merely describing the phenomenon. Consequently, existing methodological paradigms should be adapted from correlational designs toward experimental approaches, for example, with controlled manipulation of the QE duration. Subsequently, other aspects of the QE, that is, beyond the mere QE duration that merit further consideration in the future will be discussed, such as the relevance of its spatial anchoring. (übern.)